2001
DOI: 10.1039/b104311k
|View full text |Cite
|
Sign up to set email alerts
|

Polyamines containing naphthyl groups as pH-regulated molecular machines driven by light

Abstract: A series of compounds made up by linking methylnaphthalene fragments at both ends of different polyamine chains have shown to behave as pH-regulated molecular machines driven by light and fluorescence emission studies have proved the formation of an excimer between the two naphthalene units whose appearance, fluorescence intensity and decay times depend on the pH value of the media.Many biological systems can be considered as more or less complex molecular machines operated by chemical or physical stimuli. Exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
46
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 13 publications
6
46
1
Order By: Relevance
“…[9][10][11] In particular, we have observed from NMR studies, taken with the compounds here reported and also with similar systems, containing anthracene (or benzene) as the emissive chromophore instead of naphthalene, that the first proton release always takes place with the central nitrogens. [8][9][10][11] On the other hand, the protonation sequence is mainly ruled by the existence of a minimum of repulsion between equally charged species. The obtained exponential dependence for the quenching rate constant, shown in Figure 2, is of general formula, k q ) k q (0) exp(-d), leading to a factor of 0.45 Å -1 , 1-7 suggesting that electron transfer would occur at longer distances than expected for an aliphatic system.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…[9][10][11] In particular, we have observed from NMR studies, taken with the compounds here reported and also with similar systems, containing anthracene (or benzene) as the emissive chromophore instead of naphthalene, that the first proton release always takes place with the central nitrogens. [8][9][10][11] On the other hand, the protonation sequence is mainly ruled by the existence of a minimum of repulsion between equally charged species. The obtained exponential dependence for the quenching rate constant, shown in Figure 2, is of general formula, k q ) k q (0) exp(-d), leading to a factor of 0.45 Å -1 , 1-7 suggesting that electron transfer would occur at longer distances than expected for an aliphatic system.…”
Section: Resultsmentioning
confidence: 95%
“…The most intense emission occurs for the fully protonated form, and the subsequent proton removal (from the chain) leads to a decrease in the emission intensity. [9][10][11] This quenching effect is due to an intramolecular electron-transfer process involving the lone pair of a deprotonated amine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1b, the spectrum of ligand 2 exhibited a weak structureless band at 391 nm together with an intense band having a structure at 335 nm at pH 9.6, at which the ligand molecule was completely deprotonated to exist as L 2À . The 335 nm band is attributable to monomeric (or isolated) naphthyl group, and the 391 nm band to naphthyl excimer by comparison with the emission spectra reported for naphthalene derivatives [1][2][3][4][5][6][7][8][13][14][15]22]. The excimer is formed as a result of an intramolecular interaction because an intermolecular interaction is not operative for naphthalene at concentration as low as 10 À6 M [13].…”
mentioning
confidence: 99%
“…Coordination of acetate with the amide proton would bring together the naphthalene subunits and induce the appearance of the excimer emission. In other words, the new band at 450 nm could be assigned to the formation of an excimer between the two naphthalene subunits [18].…”
Section: Fluorescence Titrationsmentioning
confidence: 99%